2009
DOI: 10.1002/ibd.20808
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of basal and probiotic-inducible G-CSF in intestinal mononuclear cells is associated with inflammatory bowel disease

Abstract: These results suggest that high G-CSF production induced by commensals such as L. rhamnosus is important in maintaining normal immunological homeostasis in the intestine and defects in the production of G-CSF are associated with IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…High levels of G-CSF are constitutively expressed in normal mouse or human intestine, and an exogenous commensal probiotic, Lactobacillus rhamnosus , was able to further enhance the expression [53]. In the absence of tributyrin, we found that ethanol-exposed mice had lower expression of G-CSF in the proximal colon.…”
Section: Discussionmentioning
confidence: 92%
“…High levels of G-CSF are constitutively expressed in normal mouse or human intestine, and an exogenous commensal probiotic, Lactobacillus rhamnosus , was able to further enhance the expression [53]. In the absence of tributyrin, we found that ethanol-exposed mice had lower expression of G-CSF in the proximal colon.…”
Section: Discussionmentioning
confidence: 92%
“…However, it remains unclear how oral VSL#3 treatment leads to changes in systemic immunity and circulating TNF-␣ levels. Probiotic administration has been reported previously to induce increased intestinal production of the cytokine G-CSF (Martins et al, 2009). In our current study, consistent with this previous report, we found a striking increase in plasma G-CSF levels in VSL#3-treated BDL mice compared with placebo-treated BDL and sham mice.…”
Section: Discussionmentioning
confidence: 97%
“…Conversely, LP macrophages from IBD patients produce less of the cytokine G-CSF, which is protective in experimental models of colitis, in response to the probiotic Lactobacillus rhamnosus GR-1 compared to those from healthy controls. 134 …”
Section: Macrophages and Dcs In Ibd Pathogenesismentioning
confidence: 99%